Parasitic wasps (Hymenoptera: Chalcidoidea) of Aleyrodidae and Diaspididae (Hemiptera: Sternorrhyncha) in orange (Citrus sinensis L.) orchards of the Chontalpa region, Tabasco, Mexico. - Peralta-Gamas, Marcelino; Myartseva, Svetlana Nikolaevna; González-Hernández, Alejandro; Villanueva-Jiménez, Juan Antonio; Sánchez-Soto, Saúl; Irtiz-García, Carlos Fredy (Instituto de Ecología, A.C., 2010)
Six parasitoid species from three families of Hymenoptera were identified attacking whiteflies and armored scales on orange crops in the Chontalpa region of Tabasco, Mexico. These were: Arrhenophagus chionaspidis (Auvr.), Encarsia citrina (Craw), E. haitiensis Dozier, E. perplexa (Huang & Polaszek), Eretmocerus sp. and Signiphora sp., all of which are new records for the region and the state.